Autonomous Car using Machine Learning - Jagtap, Sharad; Bhosale, Purva; Borse, Nikhil; Borke, Samadhan; Rapartiwar, Shubham (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The autonomous car or the driverless car can be referred to as a robotic car in simple language. This car is capable of sensing the environment, navigating and fulfilling the human transportation capabilities without any human input. Autonomous cars sense their surroundings with cameras, radar, lidar, GPS and navigational paths. Advanced control systems interpret sensory information to keep track of their position even though the conditions change. The advantages of autonomous cars, such as fewer traffic collisions, increased reliability, increased roadway capacity, reduced traffic congestion as well as reduction of traffic police and care insurance, are compulsive for the development of autonomous car even though we have to overcome the issues of cyber security, software reliability, liability of damage and loss of driver related jobs. Autonomous cruise control or the Lane departure warning system and the Anti-lock braking system (ABS) are the early steps.